TEACHERS’ PERCEPTIONS OF INTERCULTURAL COMMUNICATIVE COMPETENCE (ICC) IN BUSINESS ENGLISH TEACHING - Duyen Thi Phung Ho (STKIP PGRI Jombang, 2019)
This case study was done at the College of Foreign Economic Relations (COFER) (Ho Chi Minh City, Vietnam) with six Business English teachers as participants. The study aimed to explore the teachers’ perceptions of teaching Intercultural Communicative Competence (ICC) in Business English education. The data were collected through 1/ in- depth interviews; 2/ syllabus, textbook and lesson plan analyses; 3/classroom observations. Inductive analysis was used to analyze the data. The findings revealed that despite the teachers’ acknowledgement of the importance of ICC in Business English Education, their perceptions of ICC were inadequate and so were their ICC teaching practices. The study not only enabled Business English teachers to gain a deeper insight into all the aspects of ICC but also provided educators with empirical evidence of teaching ICC in Business English, serving as a good source of data for more efficient policies to develop ICC teaching and learning in the global integration.